Occurrence of Carcinoma Prostate in Different Levels of Serum PSA ≥ 2.5 NG/ML in Bangladesh (Bangladesh Journal of Urology, 2020)
Background: Prostate cancer is the most common cancer in men. Serum prostatespecific antigen (PSA) is the screening test for the prostate cancer. This test is usually done for the first step in any prostate cancer diagnosis. Prostate biopsy is the procedure for final diagnosis of carcinoma prostate.Objective: To detect the occurrence of prostate cancer at different level of serum PSA ≥2.5ng/mlMethod: This hospital based cross sectional analytical study was conducted between the periods of January 2012 to April 2013. A total of 105 patients with features of lower urinary tract symptoms with enlarged prostate attending to the Department of Urology, National Institute of Kidney Diseases & Urology (NIKDU), Sher-E-Bangla Nagar, Dhaka were purposively selected as study population. Patients more than 50 years old with lower urinary tract symptoms at S. PSA level ≥ 2.5 ng/ml and enlarged prostate in DRE were selected as study population. Patients with bleeding disorder, anorectal pathology, active UTI or prostatitis or urethral stricture were excluded from this study. DRE was done to see the size, consistency and nodularity of prostate. Those who had enlarged prostate found on DRE having S. PSA levele” 2.5 ng/ml, they were sent for biopsy.Result: The mean age of the patients was 66.87±10.13 years with a range of 51-92 years. Among 105 patients 19 (18.10%) were in the age group of 51-60 years, 35 (33.33%) were in the age group of 61 - 70 years, 27 (25.71%) were in the age group of 71 - 80 years and 24 (22.86%) were in the age group >80 years. Among 105 patients 45 (42.9%) had malignant lesion and 60 (57.10%) had benign lesion. Mean serum PSA level among the patients with histopathological findings benign and malignant were 7.87±5.18 and 27.42±22.25 ng/ ml respectively. Out of 45 patients with malignant lesion, 3(16.7%) had serum PSA level within 2.50-2.99 ng/ml, another 5(14.3%) had 4.00-9.99 ng/ml, 11(56.0%) had serum PSA level within 10.00-20.00 ng/ml and 26(57.8%) There is a statistically significant difference observed in serum PSA level among the patients with histopathological findings benign and malignant (P